WOW asked in Science & MathematicsMathematics · 10 years ago

Explain the error made in solving the equation below. Then solve the equation correctly.?

Explain the error made in solving the equation below. Then solve the equation correctly.

(x + 2)(x – 3) = 6

x + 2 = 6 x – 3 = 6

x = 4 x = 9

5 Answers

Relevance
  • 10 years ago
    Best Answer

    You can only solve that way when the equation = 0

    Since it equals 6, you need to work it out again:

    x^2 +2x - 3x - 6 = 6

    x^2 - x - 12 = 0

    (x - 4)(x + 3) = 0

    x = 4

    x = -3

  • Anonymous
    10 years ago

    Another equals was added. That is the mistake, not to mention the random adding of a six next to the second x.

    (x + 2)(x - 3) = x^2 - x - 6

    x^2 - x - 6 - 6 = 0

    x^2 - x - 12 = 0

    (x + 3)(x - 4)

  • 10 years ago

    Thats not even remotely correct, I don't know what the person was trying to do. But I can show you how it should be done.

    (x+2)(x-3) = 6

    x^2 - x - 6 = 6

    x^2 - x - 12 = 0

    (x-4)(x+3) = 0

    x = -3, 4

    Source(s): Haha this kind of math makes me nostalgic :P
  • Anonymous
    10 years ago

    x + 2 not equals 6

    x - 3 not equals 6

    only works if (x+2)(x - 3) = 0

    Solve: FOIL it out.

    x^2 - x - 6 = 6

    x^2 - x - 12 = 0

    (x - 4)(x + 3) = 0

    x - 4 = 0 : x + 3 = 0

    x = 4, -3

  • How do you think about the answers? You can sign in to vote the answer.
  • Anonymous
    10 years ago

    i dont see how x can represent both numbers.

Still have questions? Get your answers by asking now.